Evaluasi Manajemen Risiko Syariah pada Hotel Syariah di Indonesia: Studi Ketidakselarasan Norma Hukum dan Praktik Operasional di Bogor dan Jakarta - Robbani, Hamzah; Mohamad Puad , Noor Aimi (Neolectura, 2025)
The halal trading industry is showing rapid growth, in line with the increasing demand among Muslims for services that comply with Sharia principles. In Indonesia, many hotels comply with sharia, but do not have adequate certification and supervision facilities. This phenomenon occurs incongruence between branding demands and operational practices, which creates reputational risks. Therefore, an in-depth assessment of the regulations and implementation of sharia risk management in this sector is necessary. This study uses a qualitative, normative-empirical approach, using literature review, field observations, and in-depth interviews with Sharia hotel administrators in Bogor and Jakarta. Analysis is carried out by examining regulations and identifying gaps between norms and practice. The results show that the current legal framework does not yet provide clear sectoral standards for Sharia hotels, and business entrepreneurs still have not implemented a comprehensive Halal Product Guarantee System. Various operational dilemmas, unwilling human resources, and weak internal oversight, such as the absence of halal supervisors and internal audits, have been identified. A